Further complicated histories: a revision of the Ameerega bassleri species group (Anura: Dendrobatidae) and a new species from the Cordillera Escalera of Peru - Geralds, Breann; Twomey, Evan; Deutsch, Michael S.; Chávez, Germán; Brown, Jason L. (Zootaxa, 2026)
We describe a new species of poison frog from north-central Peru that was previously considered a morph of Ameerega bassleri. Our phylogenetic results indicate that A. bassleri as currently defined is polyphyletic, with the nominal clade (A. bassleri sensu stricto) sister to A. pepperi, and a second, as yet unnamed clade, sister to A. yoshina. This latter clade contains the well-known yellow morph occurring in the mountains near Tarapoto, which for the last ca. 20 years was erroneously thought to represent the nominal form of A. bassleri. Observations of color-pattern and analyses of male advertisement call traits (note-rate and dominant frequencies) reveal consistent differences between A. pepperi, A. yoshina, and the two lineages of A. bassleri (treated as separate groups), supporting the hypothesis that these four clades are independent evolutionary lineages. Based on these results, we restrict A. bassleri to the clade containing the Chrome-green and Black morphs and describe the Yellow morph as a new species.